The relationship between childhood traumatic experiences, mental health, and substance use, among youth in Iceland - Eva Egilsdóttir 2002- (2024)
Substance use is an ongoing significant public health concern. It is a multifaceted issue, but factors such as childhood trauma and mental health have been shown to be linked to substance use. The purpose of this study is to look at the relationship between childhood traumatic experiences, mental health, and substance use among youth in Iceland, while also accounting for perceived parental financial situation and gender. Mental health was measured with anxiety and depression scales, and childhood traumatic experiences with two separate measures relative to intensity of experiences. Data was collected from youth in Iceland attending 8th, 9th, and 10th grades with survey questionaries in 2020, with this study being a secondary analysis. The results showed that increase an depression and traumatic experiences was associated with an increase in substance use. Improved perceived financial situation was associated with decreased substance use. On the other hand, anxiety showed no significant relationship to substance use (p= 0.27). Descriptively, the results also showed that boys are more likely than girls to use substances. The multivariate results suggest that addressing mental health issues and socioeconomic disparities may be important in preventing substance use, particularly among adolescent boys. Keywords: substance use, mental health, childhood traumatic experiences, parental financial situation Vímuefnaneysla er enn í dag stórt lýðheilsuvandamál. Þetta er greinilega margþætt mál, en sýnt hefur verið fram á að þættir eins og áföll í æsku og geðheilsa tengist vímuefnaneyslu. Tilgangur þessarar rannsóknar er að skoða tengsl áfallaupplifunar í æsku, geðheilsu og vímuefnaneyslu ungmenna á Íslandi, ásamt því að gera grein fyrir fjárhagsstöðu foreldra og kyns. Geðheilsa var mæld með kvíða- og þunglyndis kvarða, og áfallaupplifun í æsku með tveimur aðskildum mælikvörðum miðað við alvarleika áfalls. Rannsóknir og Greining safnaði gögnum árið 2020 frá ungmennum á Íslandi í 8., 9. og 10. bekk með spurningakönnun. ...